2023
DOI: 10.4254/wjh.v15.i6.786
|View full text |Cite
|
Sign up to set email alerts
|

Role of vascular endothelial growth factor B in nonalcoholic fatty liver disease and its potential value

Abstract: Nonalcoholic fatty liver disease (NAFLD) refers to fatty liver disease caused by liver injury factors other than alcohol. The disease is characterized by diffuse fat infiltration, including simple steatosis (no inflammatory fat deposition), nonalcoholic fatty hepatitis, liver fibrosis, and so on, which may cause liver cirrhosis, liver failure, and even liver cancer in the later stage of disease progression. At present, the pathogenesis of NAFLD is still being studied. The "two-hit" theory, represented by lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…In our study, in addition to increasing serum glucose and total cholesterol levels, diabetes induction led to a decrease in hepatic VEGF-β, which is consistent with the results of Lee et al (22). Research has shown that VEGF-β can reduce lipid accumulation and restore insulin sensitivity in NAFLD (7). Therefore, the decrease in VEGF-β caused by diabetes is related to the liver complications of diabetes such as hepatic steatosis and hepatic insulin resistance.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In our study, in addition to increasing serum glucose and total cholesterol levels, diabetes induction led to a decrease in hepatic VEGF-β, which is consistent with the results of Lee et al (22). Research has shown that VEGF-β can reduce lipid accumulation and restore insulin sensitivity in NAFLD (7). Therefore, the decrease in VEGF-β caused by diabetes is related to the liver complications of diabetes such as hepatic steatosis and hepatic insulin resistance.…”
Section: Discussionsupporting
confidence: 92%
“…With regard to the effect of the interventions on hepatic VEGF-β gene expression, our results showed that continuous aerobic exercise could increase VEGF-β gene expression compared to the control diabetes group, but atorvastatin had no significant effect on hepatic VEGF-β. Previous research has shown that VEGF-β plays a role in lipid and glucose homeostasis (7). It has been reported that body fat, serum lipoprotein, NAFLD score, and insulin resistance increased after VEGF-β knockout mice were fed a high-fat diet (22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations